269 EFFECTS OF COLCHICINE TREATMENT AFTER MYOCARDIAL INFARCTION ON TOP OF STANDARD THERAPY: EVIDENCE FROM A PRECLINICAL STUDY. (15th December 2022) - Aimo, Alberto; Burchielli, Silvia; Aquaro, Giovanni Donato; Barison, Andrea; Musetti, Veronica; Masotti, Silvia; Pucci, Angela; Galvez-monton, Carolina; Martinez-falguera, Daina; Passino, Claudio; Emdin, Michele; Bayes-genis, Antoni
Abstract: Background: An intense inflammatory and fibrotic response after myocardial infarction (MI) may lead to scar expansion and left ventricular (LV) remodeling, increasing the risk for ventricular arrhythmias and heart failure. Colchicine is an anti-inflammatory drug that has been reported to improve the outcome of patients with MI; its effects on LV remodeling have not been specifically investigated. We aimed to characterize the effects of the anti-inflammatory drug colchicine in an animal model of reperfused MI. Methods: In 4-month-old pigs, MI was induced by occluding the LAD artery through an angioplasty balloon for 90 minutes. Pigs surviving MI induction were randomized in a 1:1 fashion to 2 arms: control group (n=13): MI induction and reperfusion, standard treatment (the same therapies as in the rat study), colchicine group (n=13): MI induction and reperfusion, standard treatment plus colchicine. The pigs underwent a first CMR scan 72 hours after MI induction, and another CMR at day 30. The pigs were then sacrificed the day after the second CMR. The primary efficacy endpoint was LGE mass (as a percentage of LV mass). Results: The infarcted area at 72 hours (expressed as absolute mass or as a percentage of the LV mass) and the changes over 1 month did not differ significantly between pigs on colchicine plus standard therapy vs. those on standard therapy alone. When assessing the extent of fibrosis on the explanted hearts (as a percentage of the tissue sample areas) there was a trend toward a lower extent of myocardial fibrosis in pigs on colchicine plus standard therapy (p=0.091). The percent differences in LV volumes, ejection fraction and mass across the two CMR scans did not reach statistical difference. Conclusions: The results from a pig model of reperfused MI suggest that colchicine has no additional effects to standard MI therapy on MI size and LV remodeling.